2017 IEEE Manchester PowerTech 2017
DOI: 10.1109/ptc.2017.7980938
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methodology to develop frequency-dependent equivalents in networks with multiple converters

Abstract: This paper discusses the analysis of dynamic interactions above the fundamental frequency in networks with high penetration of converters. For this purpose, interaction studies require a good representation of network resonances and converter dynamics. However, current methodologies present some limitations in this respect. On one hand, the harmonic impedance obtained from the frequency scan in software does not consider the influence of converter control dynamics. On the other hand, typical stability studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This study showed that a low-frequency unstable oscillation appearing in the system was related to the dynamics of the outer control. In [14], dynamic interactions above the fundamental frequency were analyzed in an ac network with high penetration of MMCs, indicating the risk of unstable interactions in the high-frequency range. In [15], the interaction between an MMC-based HVDC link and an offshore wind farm was studied, showing the importance of the onshore station and dc cable dynamics for analyzing the harmonic stability of the offshore ac system.…”
mentioning
confidence: 99%
“…This study showed that a low-frequency unstable oscillation appearing in the system was related to the dynamics of the outer control. In [14], dynamic interactions above the fundamental frequency were analyzed in an ac network with high penetration of MMCs, indicating the risk of unstable interactions in the high-frequency range. In [15], the interaction between an MMC-based HVDC link and an offshore wind farm was studied, showing the importance of the onshore station and dc cable dynamics for analyzing the harmonic stability of the offshore ac system.…”
mentioning
confidence: 99%
“…In addition to the aforementioned time-delay behavior, the MMC also exhibits a steady-state time-periodic behavior, which complicates its stability assessment. In the literature, the time-periodic behavior of the MMC has at times been disregarded or simplified by neglecting part of internal converter dynamics [6], [7]. However, such simplifications result in models of limited accuracy from low to intermediate frequencies [8].…”
Section: Introductionmentioning
confidence: 99%
“…The impedance modelling methodology has been further extended to analyse the resonance and stability issues specific to wind power plants connected via converters and real experiences have highlighted critical interactions between wind farms controls and HVDC converters [20][21][22][23]. Whereas, [24] derived the analytical impedance equivalents for high frequency analysis, however without the consideration of synchronous generation. Impedance models have been well-applied to stability analysis, but not interaction analysis and dynamic responses considering hybrid AC/DC grids.…”
Section: Introductionmentioning
confidence: 99%